Pengaruh Proses Bleaching Terhadap Finishing Kayu Pinus Dan Kayu Karet Terserang Blue Stain: The Effect of Bleaching Process on Finishing of Pine Wood and Rubber Wood Attacked by Blue Stain - Mulyosari, Desy; Wijayanto, Arip; Muhamad, Soleh; Nurhanifah, Nurhanifah; Anggiriani, Siska; Fitrianto, Taufik Ramadhan; Widiyanto, Wahyu (Fakultas Kehutanan Universitas Jambi, 2025)
ABSTRACT One of the problems faced by the furniture industry is the attack of coloring fungi or what is commonly called blue stain. The attack of coloring fungi causes color changes so that the appearance of the wood decreases. The bleaching process is one way that can be done to overcome the attack of blue stain. The bleaching process in the industry uses the chemical white agent 250 (WA-250). However, research related to the effect of the bleaching process on the finishing of pine wood and rubber wood attacked by blue stain has not been carried out. This study aims to determine the effect of the bleaching process on the finishing of pine wood and rubber wood attacked by blue stain. Finishing tests include testing the adhesion of the finishing layer (cross cut test) referring to ASTM D 3359, flexibility testing is carried out with a coin test, and hardness testing refers to ASTM D 3363. The results of this study are that the bleaching process does not affect the finishing process on pine wood and rubber wood attacked by blue stain, both those treated with bleaching and those without bleaching treatment, which are included in the same finishing quality category. Based on the adhesion test, it is included in class 4B (Good) and its flexibility gets a value of 5 (very good), while the hardness of the finishing layer is in the less category. Keywords: bleaching, blue stain, finishing, pine wood, rubber wood ABSTRAK Permasalahan yang dihadapi oleh industri furnitur salah satunya adalah serangan jamur pewarna atau yang biasa disebut blue stain. Serangan jamur pewarna tersebut menyebabkan perubahan warna sehingga terjadi penurunan penampilan kayu. Proses bleaching merupakan salah satu cara yang dapat dilakukan untuk mengatasi adanya serangan blue stain. Proses bleaching pada industri menggunakan bahan kimia white agent 250 (WA-250). Namun, penelitian terkait pengaruh proses bleaching pada finishing kayu pinus dan kayu karet terserang blue stain belum dilakukan. Penelitian ini bertujuan mengetahui pengaruh proses bleaching terhadap finishing pada kayu pinus dan kayu karet yang terserang blue stain. Pengujian finishing meliputi pengujian daya lekat lapisan finishing (cross cut test) mengacu pada ASTM D 3359, pengujian fleksilbilitas dilakukan dengan coin test, dan pengujian kekerasan mengacu pada ASTM D 3363. Hasil penelitian ini adalah proses bleaching tidak mempengaruhi proses finishing pada kayu pinus dan kayu karet yang terserang blue stain baik yang diberi perlakuan bleaching maupun tanpa perlakuan bleaching masuk dalam kategori kualitas finishing yang sama. Berdasarkan uji daya lekat termasuk pada kelas 4B (baik) dan fleksibilitasnya memperoleh nilai 5 (sangat bagus), sedangkan kekerasan lapisan finishingnya kategori kurang. Kata kunci: bleaching, blue stain, finishing, kayu karet, kayu pinus